FRACTAL TRAFFIC MANAGEMENT IN WIRELESS NETWORK - Sajid Shaikh (International Journal of Innovations in Engineering Research and Technology, 2021)
Communication is significant way to move the data from one place to other place which is geographically located far away from each other. In early days telegraphy technique was used to send the information from place to other place with the help of wires. Telegraphy is very time consuming and non reliable method of data transmission. To overcome such type of problems engineers developed a new communication technology which is known as mobile communication. Mobile communication fulfils almost all the requirements of growing market and modern world. All business sectors are using mobile communication for data transmission. The new problem of fractal traffic is arrived because of limited channels and increase in fractal traffic to solve this problem traditional method is to improve the data transmission mechanism and quality of service.